PENGELOLAAN BANK SAMPAH DALAM MENDUKUNG GO GREEN CONCEPT DI DESA ULAKAN TAPAKIS KABUPATEN PADANG PARIAMAN - Bustanul Arifin; Taufiq Ihsan; Olly Norita Tetra; Nofrita Nofrita; Fadjar Goembira; Frenadin Adegustara (Jurnal Hilirisasi IPTEKS, 2020)
Waste bank management in the Nagari Ulakan community needs to be done as a solution in waste reduction, waste management and processing. The increase in tourists will increase the amount of waste in Nagari Ulakan. the problem is not the amount of waste but the disposal, management and processing of waste which is a serious problem and must be handled properly in Nagari. The purpose of this community service activity is the existence of a waste bank can provide the best solution in achieving the target of waste reduction in Nagari Ulakan, Kecamatan Tapakis, Kabupaten Padang Pariaman. The waste bank management is carried out to support the Go Green Concept through counselling on the socialization of the waste bank, the usefulness, and the stages of the preparation process for forming a waste bank. In this counselling introduced types of waste, waste sorting processes, examples of paper and plastic waste processing. The activity was followed by mentioning at the stage of forming a waste bank management and waste bank operations. The results of this activity are the reduction of waste and the formation of a waste bank in Nagari Ulakan and increasing public awareness of waste management.